A study on association between respiratory morbidity and type of work, duration of work among unorganized sector workers in Tamil Nadu - Manivannan, Tamilamudhan; Ayyappan, Chitra (International Journal Of Community Medicine And Public Health, 2024)
Background: In Tamil Nadu around 70 lakh workers including construction workers were enrolled in the e-SHRAM portal as of 31st March 2022. Occupation related respiratory disease occurs due to inhalation of dust in working place and this depends on the duration and type of work. This study aimed to find the association of respiratory morbidity with type of work and duration of work among workers in unorganized sectors in Tamil Nadu. Methods: Cross sectional study conducted among adult workers in unorganized sectors in randomly selected districts of Tamil Nadu. Results: The risk for respiratory morbidity was higher among quarry workers (AOR=9.489 with p value <0.001). The risk for restrictive lung disease among workers with a duration of work <5 years was more (OR=1.76 with 95% CI (1.14 - 2.71)). Conclusions: The risk for respiratory morbidity was high among occupations with dust exposure. This study shows that restrictive lung disease occurs within 5 years of work, hence periodic screening should be advocated from the early days of joining the workplace.